Increased Expression of Neurotrophin 4 Following Focal Cerebral Ischemia in Adult Rat Brain with Treadmill Exercise - Chung, Jin-Young (Public Library of Science, 2013)
Neurotrophin 4 (NT-4) belongs to the family of neurotrophic factors, and it interacts with the tyrosine kinase B (trkB) receptor. NT-4 has neuroprotective effects following cerebral ischemia. Its role might be similar to brain-derived neurotrophic factor (BDNF), because both interact with trkB. Exercise also improves neural function by increasing neurotrophic factors. However, expression profiles of NT-4 in the brain during exercise are unknown. Here, we assessed the expressions of NT-4 and its receptor, trkB, following cerebral ischemia and hypothesized that exercise changes the expressions of NT-4 and trkB. Results showed that in a permanent middle cerebral artery occlusion rat model, ischemia decreased NT-4 and trkB expression. Immunohistochemistry showed their immunoreactivities around the region of the ischemic area. Treadmill exercise changed the expression of NT-4, which increased in the contralateral hemisphere in rats with ischemic injury. TrkB also showed similar patterns to its neurotophins. The change in NT-4 suggested that exercise might have primed NT4 production so that further injury causes slightly greater increases in NT4 compared with non-exercise controls.